(untitled) - Farah, Mounir (Columbus, Ohio, 1999)
This book provides the reader with diluted and out of order history which does nothing except grace a classroom with twenty-five confused faces. For students to easily grasp the events of the past and the time periods between them, chronological order is vital. For example, Farah and Karls have created units that overlap significant periods of time where the "Royal Power and Conflict" chapter covers 1500-1750 and then the next chapter "Empires of Asia" covers 1350-1850.
Keywords: World history,Lịch sử thế giới